Effect of Polar Training Load-guided versus non-guided training in runners - Bruch, A.; Kinnunen, H.; Stapelfeldt, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Practical methods to quantify the individual training dose of an athlete have been studied earlier (1). Polar Training Load (TL) feature (Polar Electro Oy, Finland) aims at determining the balance between training and recovery. Input information for TL are gender, weight, VO2max, HRmax, HRrest, lactate threshold (LT), and anaerobic threshold (IAT). The training software (PPT.com) guides daily training based on individual cumulative TL values (CTL) with a colour based system (green, yellow, red). The purpose of this study was to quantify the effects of TL guidance in training and performance parameters among regularly training runners. Methods: 24 male runners were randomised into a study group (PPT.com) and a control group (PPT). The average VO2max was 59 ml/min/kg in PPT.com group and 61 ml/min/kg in PPT group. Average weekly training time before the study was 7 h in both groups. The training was followed up for 8 weeks. PPT.com group trained with TL guidance and PPT group without guidance. At the beginning and end of the study a standardized incremental maximal exercise test was performed on a treadmill (h/p/cosmos sports & medical GmbH, Germany) with respiratory gas analysis. Test measurements included LT, IAT and VO2max. One subject was left out the analysis due to training data loss. Results: Both groups trained 8.4 h/week, PPT.com with an average HR of 135 bpm, PPT group with an average HR of 133 bpm. Average CTL values before a training session were 43 and 60 in PPT.com and PPT groups, respectively, indicating a tendency towards better recovery status in PPT.com group when starting an exercise session (p = 0.08). No differences were found in any other CTL values. Lab-tests showed no significant differences between groups in any performance markers. Discussion: In runners who had been training 7 h weekly, users of TL feature didn`t train differently compared to non-users. In contrast to this, a previous study (2) showed significant changes in training among cyclists who trained 15 h weekly. One reason for the present finding may be that most runners did not train too extensively in terms of TL parameters: even without using the TL feature their own training routines did not include high intensity sessions with poor recovery status. Additionally, three subjects in PPT.com group did not adapt their training according to the TL-rules which underlines the importance of personal motivation factors.